Pengaruh Ukuran Perusahaan, Leverage, Dan Profitabilitas Terhadap Penghindaran Pajak : (Studi Empiris Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2022) - Dewi, Cikal Sari; Estrini, Dwi Hayu (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
This study aims to test the influence of company size, leverage and profitability on tax avoidance in banking companies listed on the Indonesian stock exchange in 2019-2022. This research is a quantitative research. The sampling technique uses purposive sampling. Based on a sample that meets the criteria of 117 for 4 years of observation. Then data analysis uses Microsoft Excel and SPSS 26 software. Based on research, company size and leverage have no significant effect on tax avoidance. While the profitability factor has a significant effect on tax avoidance.